Plasmodium falciparum Serine Repeat Antigen 5 (PfSERA5): current vaccine candidate for Plasmodium falciparum malaria - Ayuti Bulaan; W. Riski Widya Mulyani; Agung Nova Mahendra; I Wayan Sumardika (Intisari Sains Medis, 2020)
Background: Most of the malaria cases are caused by Plasmodium falciparum infection. The prevalence of cases and high mortality rates due to malaria should be watched out globally. However, currently, efforts to prevent and treat malaria suffer obstacles due to resistance to insecticides and antimalarial drugs. For these reasons, other preventive measures are needed, such as vaccines. This study aims to review the Plasmodium falciparum Serine Repeat Antigen 5 (PfSERA5) as a potential candidate for Plasmodium falciparum malaria vaccine development. Methods: Of the 65 journals reviewed, 51 journals were found to be suitable as references for this paper. The keywords included in selected search engines are "malaria" "PfSERA5", "Plasmodium falciparum", and "malaria vaccine". Search results and studies show that the erythrocytic phase of the vaccine can fight malaria parasites that escape the liver stage while reducing or eliminating clinical symptoms. Data were analyzed and written in a narrative form.Results: PfSERA5 is an asexual erythrocytic stage antigen that accumulates in the parasitophorous vacuole. The PfSERA5, SE47 and SE36 (modified SE47) domains can induce the formation of antibodies that protect against falciparum malaria infection in vivo and in vitro. This protective mechanism, caused by PfSERA5 (anti-SE47 and anti-SE36) specific antibodies, occurs through inhibition of parasite growth and merozoite lysis. PfSERA5 also does not show antigenic variations and has limited polymorphism, so the probability of resistance can be reduced. Conclusion: Based on this, PfSERA5 has great potential as an effective erythrocytic phase vaccine candidate. However, further studies are needed regarding the toxicological and pharmacological properties of PfSERA5, both in vivo and in clinical settings.